AB0757 Persistent crp elevation is associated with high morbidity in systemic sclerosis. (12th June 2018) - Mitev, A.; Feldmann, D.; Kanne, A.-M.; Hugle, T.; Villiger, P.M.; Voll, R.E.; Finzel, S.; Kollert, F.
Abstract : Background: Elevated levels of C-reactive protein (CRP) in systemic sclerosis (SSc) have been linked to early inflammatory stages of the disease. Objectives: This study has been set to investigate CRP levels in a longitudinal cohort of SSc patients and to correlate these findings to comorbidities and disease characteristics. Methods: In this retrospective study patients with SSc were recruited from the outpatient clinic of the Department of Rheumatology and Clinical Immunology, University Medical Centre Freiburg. Only patients with at least three consecutive visits at our centre over at least one year were included in this study. CRP serum levels were measured at every visit and categorised as positive if CRP concentrations were ≥5 mg/L. Subjects with elevated CRP levels at more than 80% of visits were defined as being persistently positive. The longitudinal CRP profile was correlated to comorbidities and disease characteristics. Results: A total of 1852 consecutive visits of 131 SSc patients were analysed. Over the observed time span (91 136–56 months) 19% (n=25) of patients had continuously elevated CRP levels, whereas in 29% (n=38) CRP levels were always in the normal range. There was no association between disease duration and CRP levels at first visit (p>0.5). Persistent CRP elevation was associated (p<0.05) with anti-topoisomerase I-antibodies, diffuse cutaneous SSc (dcSSC), modified Rodnan skin score (mRSS), pulmonary fibrosis, and cardiac arrhythmia, whereas no associations with arthritis or malignancy were found (p>0.1). In a patient with dcSSc and persistent elevated CRP even cyclophosphamide and autologous stem cell transplantation did not alter CRP levels. Conclusions: Persistently elevated CRP levels characterise a more severe fibrotic phenotype and a higher prevalence of cardiac arrhythmias. Disclosure of Interest: None declared